Influence of low frequency noise on cognitive performance tasks - M. Pawlaczyk-Łuszczyńska; A. Dudarewicz; M. Waszkowska; W. Szymczak; M. Śliwińska-Kowalska (Archives of Acoustics)
To study the influence of low frequency noise (LFN) on cognitive performance tasks, 96 subjects, categorised in terms of sensitivity to LFN, worked with four standardised psychological tests during exposure to LFN or broadband noise without dominant low frequency content (reference noise) at a level of 50 dB(A). It was found that the test results were influenced by exposure and/or noise sensitivity. Regardless of sensitivity to noise, poorer results in the LFN (compared to reference noise conditions) were noted in the Comparing of Names Test (a tendency to more erroneous responses). High-sensitive subjects achieved poorer results than others during exposure to LFN in the Stroop Colour-Word Test (a significant interaction between noise and noise sensitivity in case of reading interference) and in the Continuous Attention Test (a tendency to more erroneous reactions). These findings suggest that LFN at moderate levels could adversely influence cognitive performance tasks and subjects high-sensitive to LFN may be at highest risk.